Managed speech : the Roberts court's First Amendment - Magarian, Gregory P. (New York, NY : Oxford University Press, 2017)
This work comprehensively explores and critiques how the current US Supreme Court, under the leadership of Chief Justice John Roberts, has reshaped First Amendment law. It argues that this Court has consistently used First Amendment law to promote a limited view of freedom, while bolstering social and political stability.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 22, 2017).
Keywords: United States. -- Supreme Court; Judicial process -- United States; Freedom of speech -- United States; United States; Law; Laws of specific jurisdictions & specific areas of law